2010 5th International Symposium on Telecommunications 2010
DOI: 10.1109/istel.2010.5734156
|View full text |Cite
|
Sign up to set email alerts
|

A new hybrid algorithm for optimization based on artificial fish swarm algorithm and cellular learning automata

Abstract: Abstract-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Now we will compare our algorithm with some other metaheuristics that were considered earlier during the literature review: the artificial fish swarm algorithm based on cellular learning automata (AFSA-CLA) [15] and the evolutionary membrane algorithm (EMA) [13].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Now we will compare our algorithm with some other metaheuristics that were considered earlier during the literature review: the artificial fish swarm algorithm based on cellular learning automata (AFSA-CLA) [15] and the evolutionary membrane algorithm (EMA) [13].…”
Section: Methodsmentioning
confidence: 99%
“…We have carried out the given comparison with metaheuristics of those authors who presented the results of computing experiments with standard test functions from ones given in Table 1. To provide equal conditions with the experiments described in the papers [13,15], the values given in the table were obtained after 300,000 function evaluations. A dash in a cell means that, for the given function, experimental data is absent.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Huadong Chen et al, [24] reported a hybrid algorithm to train forward neural network using a hybrid of artificial fish swarm algorithm and particle swarm optimization. In [25], a new algorithm is proposed for optimization in continuous and static environments by hybridizing cellular learning automata and artificial fish swarm algorithm. Experimental results show that proposed method has an acceptable performance.…”
Section: Related Workmentioning
confidence: 99%
“…According to this property, AFSA model was proposed by Free-Movement, Food-Search, Swarm-Movement and Follow Behaviors in order to search the problem space. This algorithm is used in different applications [6] such as neural networks [7,8], color quantization [9], dynamic optimization problems [10], physics [11], global optimization [12][13][14][15], and data clustering [16].…”
mentioning
confidence: 99%